Natural Antimicrobials and Oral Microorganisms: A Systematic Review on Herbal Interventions for the Eradication of Multispecies Oral Biofilms - Karygianni, Lamprini; Al-Ahmad, Ali; Argyropoulou, Aikaterini; Hellwig, Elmar; Anderson, Annette C.; Skaltsounis, Alexios L. (Frontiers in Microbiology, 2016)
Oral diseases such as caries and periodontitis are mainly caused by microbial biofilms. Antibiotic therapy has reached its limits with regard to antimicrobial resistance, and new therapeutic measures utilizing natural phytochemicals are currently a focus of research. Hence, this systematic review provides a critical presentation of the antimicrobial effects of various medicinal herbs against in vitro, ex vivo and in situ formed multispecies oral biofilms. Searches were performed in three English databases (PubMed, EMBASE, CAMbase) and the electronic archives of five German journals from the times of their establishment until October 10th, 2014, with the search terms “(plant extracts OR herbal extracts OR plant OR herb) AND (oral biofilm OR dental biofilm OR dental plaque OR oral disease OR dental disease)”. The pooled data were assessed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Initially, 1,848 articles were identified, out of which 585 full-text articles were screened, 149 articles were reevaluated for eligibility and finally, 14 articles met all inclusion criteria. The data of 14 reports disclosed enhanced antiadhesive and antibiofilm activity by the plant extracts obtained from Vitis vinifera, Pinus spp., Coffea canephora, Camellia sinensis, Vaccinium macrocarpon, Galla chinensis, Caesalpinia ferrea Martius, Psidium cattleianum, representative Brazilian plants and manuka honey. Overall, a positive correlation was revealed between herb-based therapies and elimination rates of all types of multispecies oral biofilms. In that context, integrating or even replacing conventional dental therapy protocols with herbal-inspired treatments can allow effective antimicrobial control of oral biofilms and thus, dental diseases.